An Overview of Engineered Hydrogel-Based Biomaterials for Improved β-Cell Survival and Insulin Secretion - Ghasemi, Azin; Akbari, Elham; Imani, Rana (Frontiers in Bioengineering and Biotechnology, 2021)
Islet transplantation provides a promising strategy in treating type 1 diabetes as an autoimmune disease, in which damaged β-cells are replaced with new islets in a minimally invasive procedure. Although islet transplantation avoids the complications associated with whole pancreas transplantations, its clinical applications maintain significant drawbacks, including long-term immunosuppression, a lack of compatible donors, and blood-mediated inflammatory responses. Biomaterial-assisted islet transplantation is an emerging technology that embeds desired cells into biomaterials which are then directly transplanted into the patient, overcoming the aforementioned challenges. Among various biomaterials, hydrogels are the preferred biomaterial of choice in these transplants due to their ECM-like structure and tunable properties. This review aims to present a comprehensive overview of hydrogel-based biomaterials that are engineered for encapsulation of insulin-secreting cells, focusing on new hydrogel design and modification strategies to improve β-cell viability, decrease inflammatory responses and enhance insulin secretion. We will discuss the current status of clinical studies using therapeutic bioengineering hydrogels in insulin release and furthermore, we will discuss prospective approaches.